A role for histones H2A/H2B in chromatin folding and transcriptional repression. - Hansen, J C (1994)
Histone octamers or histone H3/H4 tetramers were reconstituted onto either closed circular plasmids containing a single Xenopus 5S rRNA gene or a reiterated array of Lytechinus 5S rRNA genes. All "reconstitutes" were found to undergo both Na(+)-dependent and Mg(2+)-dependent compaction. However, in each case, the compaction of nucleosomal templates containing H2A/H2B was much more extensive than compaction of templates containing only H3/H4 tetramers. Inclusion of 5 mM MgCl2 in the transcription buffer increased the level of compaction of nucleosomal templates and led to a marked inhibition of both transcription initiation and elongation by RNA polymerase III. The inhibitory effect of Mg2+ was reduced significantly when DNA templates contained only H3/H4 tetramers, consistent with their lesser extent of Mg(2+)-dependent compaction. Thus, the removal of histones H2A/H2B from nucleosomal arrays enhances gene activity, in part because of decreased levels of chromatin folding.